A súmula vinculante e sua (in)compatibilidade com o princípio constitucional da legalidade - Lanes, Andreotte Norbim (2008)
This study aims at verifying the compatibility between biding abridgement and the constitutional principle of legality, which claims that “no one shall be required to do or not to do something, unless it is by virtue of the law” (article 5, II, of the Brazilian Federal Constitution). Since the juridical system adopted by the Brazilian civil law does not allow binding force to any other instrument but the law, and the fact that the binding abridgement is edited by a body deprived of typically legislative function, we adopted a hypothetical-deductive approach in this study. It started with a scientific knowledge problem, passing through hypotheses formulation and through a deductive inference process, which tests the hypothesis. Thus, it was necessary the use of the comparative procedure method (investigating the similarities and differences between different legal instruments) and the monographic method (where certain juridical mechanisms were analyzed from various angles). The references used were bibliographical and documental and the Internet, through books, articles and the legislation in force. The result shows that even though binding abridgements have jurisdictional isonomy, process celerity and juridical security as background, they are incompatible with all the national juridical system, as well as with the strictly law-abiding constitutional principle, since it is the only acceptable in civil law.